2012
DOI: 10.1111/j.1349-7006.2012.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of DJ‐1 protein in nipple fluid of patients with breast cancer

Abstract: As we have previously demonstrated that some breast cancer cell lines secrete DJ-1 protein, we examined here whether breast cancer cells secrete DJ-1 protein in vivo. To this end, the levels of DJ-1 protein present in 136 specimens of nipple fluid was examined by enzyme-linked immunosorbent assay (ELISA). The average concentration of DJ-1 protein detected in diluted samples from 47 patients with invasive ductal carcinoma (IDC) was 22.4 ng/mL, while it was 18.6 ng/mL in 26 patients with ductal carcinoma in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, recently DJ-1 has emerged as a significant biomarker since its presence has been detected in the serum of gastric cancer [99], prostate carcinomas [100], pancreatic cancer [101], non-small cell lung cancer [102] and uveal melanoma [103] patients. Similarly, higher DJ-1 levels have been noted in nipple secretions from breast carcinoma patients [104]. Moreover, DJ-1 has been detected in cerebrospinal fluid from Parkinson’s Disease patients [105], [106], [107] and urine from hepatocellular carcinoma [108] patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, recently DJ-1 has emerged as a significant biomarker since its presence has been detected in the serum of gastric cancer [99], prostate carcinomas [100], pancreatic cancer [101], non-small cell lung cancer [102] and uveal melanoma [103] patients. Similarly, higher DJ-1 levels have been noted in nipple secretions from breast carcinoma patients [104]. Moreover, DJ-1 has been detected in cerebrospinal fluid from Parkinson’s Disease patients [105], [106], [107] and urine from hepatocellular carcinoma [108] patients.…”
Section: Discussionmentioning
confidence: 98%
“…DJ-1 is a novel mitogen-dependent oncoprotein involved in Ras-related signal transduction pathway,11 which has been confirmed to be upregulated in multiple cancers 12,13. In the current study, it was found that high DJ-1 expression level is an independent prognostic factor for IHCC patients.…”
Section: Discussionsupporting
confidence: 53%
“…DJ-1 has been reported to be overexpressed in several types of human cancer, including lung cancer 24, breast cancer 25, pancreatic cancer 26, esophageal carcinoma 27, and bladder tumors 10. It has also demonstrated that DJ-1 improves tumor cell survival by modulating the Akt/PI3K axis 17, inhibiting apoptosis through repression of the p53-Bax-caspase pathway 28 and stabilizing the antioxidant transcriptional master regulator Nrf2 29.…”
Section: Discussionmentioning
confidence: 99%